Fungitoxic Potentials of Ocimum Gratissimum L. and Zingiber Officinale (L.) Roscoe Extracts Against Fungi Associated with Postharvest Rot of Carica Papaya L. - Sobowale, A. A.; AGBANE, John; BAMKEFA, Bukola Ayodeji; ADURAMIGBA-MODUPE, Adefoyeke Olufunmilayo (European Journal of Applied Sciences, 2022)
The fungitoxic potentials of Ocimum gratissimum and Zingiber officinale extracts on fungi associated with rotting Carica papaya were investigated. Rotting and healthy pawpaw species of Carica papaya were obtained from Bodija market, Ibadan, Nigeria. Isolation of fungi from the rotting fruit was done using standard procedures. Pure cultures of the isolated fungi were obtained on Acidified Potato Dextrose Agar (APDA). Leaves of O. gratissimum and rhizome of Z. officinale were obtained from Botanical Garden, University of Ibadan, Nigeria. Crude extracts (aqueous and methanol) of the plants were obtained using standard procedures. The antimicrobial potentials of the extracts on the isolated fungi in vitro at concentrations of 25%, 50%, 75% and 100% were evaluated. Their interactive effects on the pathogens were also evaluated. Cultures with 0% methanol and water served as controls. All experiments were done in triplicates. Incubation of all Petri plates were done at room temperature for 7 days. Radial and diametric growth of the fungi was measured every 24 hours using a meter rule. Data obtained were subjected to analysis using SAS (version 9.2). Mean separation was done using Duncan Multiple Range Test (DMRT) at p≤0.05). The isolated fungi were Colletotrichum gloeosporioides, Lasiodiplodia theobromae, and Aspergillus flavus. Inhibitory effects of extracts of both plants and of both solvents on the isolated pathogens were significantly better than in control. Inhibitory effect of the methanol extracts was better than that of aqueous extracts. Inhibitory effect of O. gratissimum extract was also significantly better than that of Z. officinale (p≤0.05). Inhibition at all extract concentrations was significantly better than in control. However, inhibition at 100% and 75% was higher than that at other concentrations. Inhibition obtained with the different treatment combinations was better than that with individual concentrations. Generally, inhibition of Lasiodiplodia theobromae was significantly better than that of Aspergillus flavus, which in turn was significantly better than that of Colletotrichum gloeosporioides (p≤0.05). Ocimum gratissimum and Zingiber officinale could be said to possess promising fungitoxic potentials. More work is required to ascertain their potentials in vivo.